2009
DOI: 10.3349/ymj.2009.50.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Higher Lesion Detection by 3.0T MRI in Patient with Transient Global Amnesia

Abstract: Purpose: Transient global amnesia (TGA) patients were retrospectively reviewed to determine the usefulness of high-field strength MRI in detecting probable ischemic lesions in TGA. Materials and Methods: We investigated the lesion detection rate in patients with TGA using 1.5T and 3.0T MRI. Acute probable ischemic lesions were defined as regions of high-signal intensity in diffusion weighted image with corresponding low-signal intensity in apparent diffusion coefficient map. Results: 3.0T MRI showed 11 out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…There was only one study evaluating the potential influence of the magnetic field strength on the lesion detectability of DWI in TGA [30]. However, the precise comparison of the influence of the magnetic field strength was difficult to assess in their study because the imaging parameters including the matrix, field of view, section thickness, and resulting voxel size were different between 1.5-and 3-T examinations.…”
Section: Discussionmentioning
confidence: 94%
“…There was only one study evaluating the potential influence of the magnetic field strength on the lesion detectability of DWI in TGA [30]. However, the precise comparison of the influence of the magnetic field strength was difficult to assess in their study because the imaging parameters including the matrix, field of view, section thickness, and resulting voxel size were different between 1.5-and 3-T examinations.…”
Section: Discussionmentioning
confidence: 94%
“…The full-text review further excluded 6 more articles: 3 that did not include DWI, 1 that was not written in English, 1 that included fewer than 5 patients, and 1 that included incomplete information. Finally, 22 eligible articles (1732 patients) were included in this meta-analysis [2,[6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Figure 1 shows the detailed study selection process.…”
Section: Literature Searchmentioning
confidence: 99%
“…Other investigators have found frontal lobe abnormalities by diffusionweighted MRI [38] or PET imaging [39]. Several reports have described diffusion-weighted imaging (DWI) lesions in a high proportion of TGA cases, especially hippocampal abnormalities [39][40][41][42]. The last article cited reported a higher detection rate, 11/32 compared with 0/32 with 3 T MRI, compared with 1.5 T. The experience in our hospital has been less positive, in that most patients have had negative DWI MRI scans.…”
Section: Introductionmentioning
confidence: 99%